Wealth, inheritance, and concentration: An "old" new perspective on Italy and its regions from unification to the Great War - Giacomo Gabbuti; Salvatore Morelli (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2023)
Despite its relevance in 19th-century economics, wealth -its accumulation, composition, and distribution- has largely been neglected in Italian economic history. Filling this gap, we show that between the late 19th and mid-20th centuries, Italy presented a historically high value of total private wealth but had relatively small relevance in total bequests flows in proportion to national income. Then, we present novel estimates of wealth concentration between 1863 and 1914, combining national tabulations of inheritance tax records and microdata archives for Milan and Naples. During this period, wealth concentration in Italy was in line with the highest levels ever recorded since the late Middle Ages. Contrary to the evidence of declining income inequality in the period -traditionally considered the industrial 'take-off' phase of Italy- we find no clear signs of trends in wealth concentration or structural changes in wealth composition. This picture is confirmed and enriched by novel findings about wealth concentration at provincial and regional levels in the early 20th century. We show a great deal of heterogeneity beyond national aggregates but find no evidence of the classic North-South divide when looking at concentration. Likewise, we find no clear link between concentration levels and asset composition or economic development. Although contemporary inequality is much lower than early 20th-century figures, the 'real' wealth of present 'millionaires' seems much higher than that of historically rich individuals. Overall, the paper lays the basis for a very long-run view of wealth in Italy and reconsiders the impact of its industrialization at the end of the Liberal period.
Keywords: D31; D63; E21; H24; N33; 330; inequality; inheritance; wealth; Liberal Italy; Southern Question